2013
DOI: 10.1021/es3052284
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Electric Power Production Utilizing Natural Gas, Renewables and Carbon Capture and Sequestration on U.S. Freshwater Resources

Abstract: Carbon capture and sequestration (CCS) has important implications relative to future thermoelectric water use. A bounding analysis is performed using past greenhouse gas emission policy proposals and assumes either all effected capacity retires (lower water use bound) or is retrofitted (upper bound). The analysis is performed in the context of recent trends in electric power generation expansion, namely high penetration of natural gas and renewables along with constrained cooling system options. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Currently it accounts for about 5% of the nation's water consumption and has the potential to both increase or decrease slightly depending on the mix of fuel type and cooling type adopted along with the mix of plants retired (e.g. Tidwell et al 2013). Most western states had estimated changes in consumptive water use by agricultural irrigation, while only Arkansas provided such values in the east (no attempt was made here to independently estimate changes to irrigation).…”
Section: Data Limitationsmentioning
confidence: 99%
“…Currently it accounts for about 5% of the nation's water consumption and has the potential to both increase or decrease slightly depending on the mix of fuel type and cooling type adopted along with the mix of plants retired (e.g. Tidwell et al 2013). Most western states had estimated changes in consumptive water use by agricultural irrigation, while only Arkansas provided such values in the east (no attempt was made here to independently estimate changes to irrigation).…”
Section: Data Limitationsmentioning
confidence: 99%
“…These changes, in turn, may be driven in part by future water policies, which could affect estimated water impacts. Following Macknick et al (2012) and Tidwell et al (2013), new power plants modeled in ReEDS do not have the option of installing once-through cooling technologies.…”
Section: Water Use Reduction Benefitsmentioning
confidence: 99%
“…www.sciencedirect.com Current Opinion in Chemical Engineering 2014, 5:7-14 futures with a focus on the role of CCS in meeting varying CO 2 reduction goals [18]. Their bounding analysis considered either all affected capacity to be retired or retrofitted with CCS and found that for 2035 nationwide withdrawals could either increase 1% or decrease 60% relative to 2009 levels, but consumption could increase up to 21% or decrease 28%.…”
Section: Long-term System-level Trends In Water For Energymentioning
confidence: 99%
“…As the literature has looked ahead to future water demands, studies have attempted to project water use in the context of global climate change and its implications for the water resources upon which the electric sector depends. Beyond the water-energy nexus, complex combinations of terms have become common, including the electricity-water-climate change nexus [15,16], electricity-water tradeoffs [17], CCS-water nexus [18], water-CO 2 tradeoffs [19 ], as well as the water-energyfood nexus [20] and even the society-biosphere-climateeconomy-energy system [21]. All of these combinations underscore the systems-level perspective as well as the diversity of modeling approaches that are used to quantify these linkages.…”
Section: Introductionmentioning
confidence: 99%